The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/adma.202002254
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Transport Correlation Reveals Anisotropic Charge Transport in Coupled PbS Nanocrystal Superlattices

Abstract: The assembly of colloidal semiconductive nanocrystals into highly ordered superlattices predicts novel structure‐related properties by design. However, those structure–property relationships, such as charge transport depending on the structure or even directions of the superlattice, have remained unrevealed so far. Here, electric transport measurements and X‐ray nanodiffraction are performed on self‐assembled lead sulfide nanocrystal superlattices to investigate direction‐dependent charge carrier transport in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 39 publications
0
29
0
1
Order By: Relevance
“…[ 16 ] In this scheme, the MDHs hold promises for the photoredox reactions enabled by the shuttling of electrons between subunits (NRs and NTs), followed by rapid accumulation at active sites. [ 17 ] Additionally, MDHs‐AR4 has the most efficient electron transfer and largely inhibited backward recombination, which is probably due to the optimized structures from self‐assembly. The interlock arrangement of the NRs within the NTs gave rise to strong electronic coupling between adjacent particles, while the spacing between the NTs and NRs reduced interparticle recombination (Figure S15, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 ] In this scheme, the MDHs hold promises for the photoredox reactions enabled by the shuttling of electrons between subunits (NRs and NTs), followed by rapid accumulation at active sites. [ 17 ] Additionally, MDHs‐AR4 has the most efficient electron transfer and largely inhibited backward recombination, which is probably due to the optimized structures from self‐assembly. The interlock arrangement of the NRs within the NTs gave rise to strong electronic coupling between adjacent particles, while the spacing between the NTs and NRs reduced interparticle recombination (Figure S15, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the direction‐dependent charge carrier transport in PbS NP supercrystals has been quantified. [ 268 ] To this end, the XCCA results have been correlated with the electronic properties of the same domains. The authors found a clear impact of supercrystal crystallinity on the electric conductivity.…”
Section: X‐ray Scattering Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] As a result, researchers have found that utilizing controlled self-assembly can lead to astounding new materials with exciting properties and unique function-alities. [9][10][11] This is not only restricted to isotropic spherical nanoparticles, which usually self-assemble into close-packed superlattices, but is especially true for anisotropic nanocrystals, which have shown to achieve even more complex superstructures and directional properties. [12][13][14] Controlled self-organization on the nanoscale has already been observed many years ago within the internal structure of BaSO 4 or rodlike particles of Ce IV minerals.…”
Section: Introductionmentioning
confidence: 99%